Indoor health and comfort for the green workplace at the university - Dyah Kusuma Wardhani; Susan; Michelle Anastasia; Michele Julian Setiando (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2020)
Greenship Interior Space is a rating tool used in ensuring more sustainable and healthy indoor space with the focus on the health and comfort of the users thermally, visually, and acoustically. It is important to study this concept further to ensure a healthier workspace where most workers spend 80-90% of their time. This is necessary because a well-designed Indoor Health and Comfort has the ability to prevent the emergence of Sick Building Syndrome and increase employee productivity. This research was conducted using the Ciputra University workplace as a case study. Moreover, a descriptive quantitative approach was implemented with data collected through observation, interviews, and field measurements. The results showed the possibility of optimizing the visual comfort and outside view in the workplace to obtain the appropriate level of illumination and to improve workers’ productivity. This, therefore, means, a workplace needs to address the environmentally and socially conscious behavior and also support employee performance in order to improve productivity in line with the strategies of a green workplace.